Retreatment efficacy of endodontic bioceramic sealers : a review of the literature = Eficacia del retratamiento de cementos endodónticos biocerámicos: revisión de Literatura - Kakoura, Flora
The endodontic retreatment is a feasible solution when post-operative apical periodontitis persists or develops. The complete removal of the filling materials is important in order to ensure the unobstructed contact of the intracanal disinfectants with the microbes. As a new generation of bioceramic endodontic sealers has emerged, their removal efficacy from the root canal system during retreatment is a matter of concern among clinicians. The aim of this article is to provide a comprehensive review of the current literature on the retreatability of these novel obturating materials. A significant amount of bioceramic sealer remnants in the root canal walls was observed in all studies. Even though canal cleanliness could not be obtained at an ideal level, the re-establishment of the working length and patency can be considered manageable and comparable to other endodontic sealers.